The good Muslim : reflections on classical Islamic law and theology - Siddiqui, Mona (Cambridge University Press, 2012)
"This thought-provoking book reflects upon key themes in Islamic law and theology to reveal fascinating insights into Islamic ethics and the way arguments developed in medieval juristic discourse. Siddiqui, who is an astute and articulate interpreter, explains the relevance of these ideas for the contemporary world"--